2017
DOI: 10.1093/jac/dkx130
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of daptomycin combinations with cephalosporins or gentamicin against Streptococcus mitis group strains in an in vitro model of simulated endocardial vegetations (SEVs)

Abstract: Addition of ceftriaxone or ceftaroline to daptomycin improves the bactericidal activity against S. mitis group strains and prevents daptomycin resistance emergence. Further investigation with combinations of daptomycin and β-lactams in a large number of strains is warranted to fully elucidate the clinical implications of such combinations for treatment of S. mitis group IE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…Although the mechanisms of DAP r in the S. mitis group seem to differ substantially from those involved in DAP r in Staphylococcus aureus and enterococci, as explained above, there is an interest for future study to look into whether combinations of DAP plus ␤-lactams, such as ampicillin or ceftriaxone, are synergistic against S. mitis and could prevent the development of DAP r . To this point, Yim et al (19) recently showed that the combination of DAP plus ceftaroline was synergistic and bactericidal against two prototypic S. mitis/S. oralis strains (S.MIT/ORALIS-351 and SF100) in an ex vivo model of simulated endocardial vegetations (SEVs) and also prevented the development of DAP r in both strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanisms of DAP r in the S. mitis group seem to differ substantially from those involved in DAP r in Staphylococcus aureus and enterococci, as explained above, there is an interest for future study to look into whether combinations of DAP plus ␤-lactams, such as ampicillin or ceftriaxone, are synergistic against S. mitis and could prevent the development of DAP r . To this point, Yim et al (19) recently showed that the combination of DAP plus ceftaroline was synergistic and bactericidal against two prototypic S. mitis/S. oralis strains (S.MIT/ORALIS-351 and SF100) in an ex vivo model of simulated endocardial vegetations (SEVs) and also prevented the development of DAP r in both strains.…”
Section: Discussionmentioning
confidence: 99%
“…This has raised the notion of using daptomycin (DAP) for the treatment of invasive S. mitis group infections. Recent studies have somewhat dampened the enthusiasm for the latter approach, as many S. mitis group strains have a unique propensity to evolve rapid, durable, and high-level daptomycin resistance (DAP r ) in vitro, ex vivo, and in vivo (17)(18)(19). This study investigated the impact of the acquisition of DAP r upon both the intrinsic fitness and survivability during treatment with DAP of such strains in a model of IE featuring coinfection with a DAP-susceptible (DAP s ) parental S. mitis/S.…”
mentioning
confidence: 99%
“…DAP is a cyclic lipopeptide antibiotic that has been broadly utilized for severe Gram-positive infections, including Staphylococcus aureus and enterococci (11). We have previously demonstrated that combinations of DAP plus ceftaroline (CPT) or ceftriaxone (CRO) are synergistic both in vitro and in the simulated endocardial vegetation (SEV) model against two well-characterized DAP-S S. mitis/oralis parental strains (the penicillin-resistant S. mitis/oralis strain, 351, and the penicillin-susceptible strain S. mitis/oralis SF100) (19). This model has the advantage of being able to precisely simulate human antibiotic concentrations to replicate therapeutic regimens used to treat specific infections (19)(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…However, following exposure to daptomycin in monotherapy, rapid development of HLDR occurs in at least 25% of S. mitis group strains in vitro; this phenomenon was replicated in vivo in EE (15). Of interest, recent investigations utilizing either the rabbit IE model or an ex vivo model featuring simulated endocardial vegetations suggest that daptomycin plus gentamicin (15) or daptomycin plus advanced-generation cephalosporins (ceftriaxone or ceftaroline) (17), respectively, can circumvent emergence of HLDR in VGS strains; however, clinical data for such combinations are lacking. We found that daptomycin plus ampicillin was synergistic in time-kill curves against both tested strains; however, HLDR was detected twice in SPAR-8497 residual after this exposure.…”
Section: Discussionmentioning
confidence: 99%